MRI validated echocardiographic technique to measure total cardiac volume: A tool for donor–recipient size matching in pediatric heart transplantation. (12th March 2013) - Camarda, Joseph; Saudek, David; Tweddell, James; Mitchell, Michael; Woods, Ronald; Otto, Michelle; Simpson, Pippa; Stendahl, Gail; Berger, Stuart; Zangwill, Steven
Abstract Our aim is to develop and validate an accurate method for estimating TCV using standard echocardiographic imaging that can be easily employed to aid in donor–recipient size matching in pediatric heart transplantation. Thirty patients who underwent Echo and cardiac magnetic resonance imaging (cMRI) were identified. TCV was measured on cMRI. TCV was determined echocardiographically by two methods: a volume measurement using the modified Simpson's method on a four‐chamber view of the heart; and a calculated volume measurement which assumed a true‐elliptical shape of the heart. These two methods where compared with the value obtained by cMRI using the concordance correlation coefficient (CCC). TCV by method 1 correlated well with cMRI (CCC = 0.98%, CI = 0.97, 0.99). TCV by method 2 had a CCC = 0.90 (CI = 0.9464, 0.9716) when compared to cMRI. Left ventricular end‐diastolic volume (LVEDV) also correlated as a predictor of TCV in patients with structurally normal hearts and could be described by the equation: TCV = 6.6 (LVEDV) + 12 (R2 = 0.97). Echocardiographic assessment of TCV for recipients and their potential donors is a simple process and can be prospectively applied as part of donor evaluation.